Medial prefrontal cortex supports source memory for self-referenced materials in young and older adults - Leshikar, Eric D. (2014)
Behavioral evidence suggests that young and older adults show a benefit in source memory accuracy when processing materials in reference to the self. In the young, activity within the medial prefrontal cortex supports this source memory benefit at study. This investigation examined whether the same neural regions support this memory benefit in both age groups. Using fMRI, participants were scanned while studying and retrieving pictures of objects paired with one of three scenes (source) under self-reference and other-reference conditions. At the time of study, half of the items were presented once and half twice, allowing us to match behavioral performance between groups. Both groups showed equivalent source accuracy benefit for objects encoded self-referentially. Activity in the left dorsal medial prefrontal cortex supported subsequent source memory in both age groups for the self-referenced relative to the other-referenced items. At the time of test, source accuracy for both self- and other-referenced items was supported by a network of regions including the precuneus in both age groups. At both study and test, little in the way of age-differences emerged, suggesting that when matched on behavioral performance young and older adults engage similar regions in support of source memory when processing materials in reference to the self; however, when performance was not matched, age differences in functional recruitment were prevalent. These results suggest that by capitalizing on preserved processes (self-referential encoding), older adults can show improvement in memory for source details which typically are not well remembered relative to the young.